Genetic factors and manganese-induced neurotoxicity - Chen, Pan; Parmalee, Nancy; Aschner, Michael (Frontiers in Genetics, 2014)
Manganese (Mn), is a trace metal required for normal physiological processes in humans. Mn levels are tightly regulated, as high levels of Mn result in accumulation in the brain and cause a neurological disease known as manganism. Manganism shares many similarities with Parkinson’s disease (PD), both at the physiological level and the cellular level. Exposure to high Mn-containing environments increases the risk of developing manganism. Mn is absorbed primarily through the intestine and then released in the blood. Excessive Mn is secreted in the bile and excreted in feces. Mn enters and exits cells through a number of non-specific importers localized on the cell membrane. Mutations in one of the Mn exporters, SLC30A10 (solute carrier family 30, member 10), result in Mn induced toxicity with liver impairments and neurological dysfunction. Four PD genes have been identified in connection to regulation of Mn toxicity, shedding new light on potential links between manganism and PD.